Analisis Kesesuaian Materi Virus Pada Buku Biologi SMA Kelas X Kurikulum Merdeka 2022 - Madalena, Dea Kristia; Indrianti, Mei; Dinillah, Rafika; Febriani, Bellatrix; Suryanda, Ade (Faktor : Jurnal Ilmiah Kependidikan, 2024)
The purpose of this study is to describe the suitability of the class X biology textbook virus material with the Natural Science Teacher's Handbook for Class X High School published by the Ministry of Education and Culture of Research and Technology on the aspects of the breadth and depth of the material. The samples used were textbook A and textbook B. Data collection through documentary research with analysis of textbook content. Research data in the form of the suitability of viral material in textbooks is reviewed from the aspects of breadth and depth of material analyzed descriptively qualitatively. The results showed that Textbook A is in the "reasonable" category for its breadth and depth, namely the breadth of "appropriate" (80%) and the breadth of "appropriate" (75%). Textbook B is in the "moderately appropriate" category (60%) for the breadth of the material, and in the "appropriate" category for the depth of matter at the 70% category. Thus, textbook A and textbook B can be used as mandatory textbooks for students.